Late replicative intermediates are accumulated during simian virus 40 DNA replication in vivo and in vitro. - Seidman, M M (1979)
Simian virus 40 (SV40) replicating chromosomes were extracted from nuclei of infected cells. The chromosomes in the extract were resolved on neutral sucrose gradients, and the extent of replication of the DNA in the chromosome peaks was determined. The extract, in combination with cytosol factors and the appropriate precursors, supports the continued replication of viral DNA. The products of the incubation were mature form I DNA and molecules (after deproteinization) with sedimentation coefficients, in neutral sucrose, of 22S and 29S. The results of our analysis of this system indicate the following. (i) The 22S molecule, which has been described by previous workers, is a relaxed, replicating molecule and is an artifact of the in vitro system. (ii) When the in vitro synthesis is performed at optimal ionic strength (150 mM potassium acetate), the artifactual 22S molecule does not appear. (iii) Late replicative intermediates do accumulate in vivo and in vitro. The major late form accumulated is 91% completed. (iv) The replicating chromosomes can be resolved into two distinct peaks on neutral sucrose gradients. The molecules in these peaks differ in extent of replication. (v) The nuclear extraction procedure preferentially extracts early replicating chromosomes. The relevance of these data to the problem of SV40 and cellular chromosome replication and termination is described.